Analisa Postur Kerja di PT. Karunia Selaras Abadi dengan Metode CMDQ, OWAS dan REBA - Aldy Tasandy Andriansyah; Boy Isma Putra (Jurnal Optimalisasi, 2023)
PT. Karunia Selaras Abadi is a flexible packaging converting company. This company produces various types of plastic packaging for snacks, powdered drinks, soap, etc. This company produces more than 10,000 rolls and 1,000,000 bags every week so that the printing cylinders at PT. The Gift of Eternal Harmony reaches more than 3,000 items. The cylinder washing process is stressful for workers, thereby triggering fatigue which results in decreased productivity. Workers handle materials incorrectly using Manual Material Handling, causing workers to experience pain in their body parts. Workers' muscles receive continuous static loads over a long period of time, potentially resulting in musculoskeletal disorders. Thus, workers are asked to fill out the CMDQ questionnaire which aims to determine the level of ergonomic risk. Based on the CMDQ questionnaire, the body parts that workers often experience pain are the knee (left), shoulder (right) and lower back. Followed by an assessment of work posture using the OWAS method including the back, arms, legs and load, then completed with an assessment of work posture using the REBA method. There are 2 activities that have a high level of risk according to the OWAS method, washing cylinders using category 3 solvent, checking cylinders, category 3. For research on the REBA method, washing cylinders using solvents with a score of 8, checking cylinders with a score of 10, these results show that all activities require an improvement process.